PENGARUH KEPERCAYAAN TERHADAP KESETIAAN PELANGGAN YANG DI MEDIASI OLEH KEPUASAN DAN KOMITMEN PELANGGAN - Tanesya Nandyastuti Wibowo; Waluyo Budi Atmoko; Ariefah Yulandari (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
This study aims to examine the effect of trust on customer loyalty which is mediated by satisfaction and commitment. Customer loyalty to a product is reflected in the customer's habit to buy products continuously. Conversely, loyal customers mean a lo t to vendors, because the cost of acquiring new customers is more expensive than maintaining existing customers. Data were collected through a questionnaire distributed to Ella skin care customers. The research sample was 200 customers at Ella skin care. The sampling technique used istwo stage cluster sampling and hypothesis testing was carried out using Structural Equation Modeling (SEM). The test results show that all hypotheses are supported, that means consumer loyalty to a brand is caused by satisfaction and commitment to a company that is formed by trust.